Diagnosis values of Dectin-1 and IL-17 levels in plasma for invasive pulmonary aspergillosis in bronchiectasis - He, Qian; Li, Min; Cao, Jiaqi; Zhang, Ming; Feng, Chunlai (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Among immunocompetent patients, patients with bronchiectasis are considered to be a high-risk group for invasive pulmonary aspergillosis(IPA). Early diagnosis and treatment can improve the prognosis of patients. Objectives: We aimed to investigate the diagnostic value of Dectin-1 and IL-17 for diagnosing IPA with bronchiectasis Methods: We retrospectively collected data on patients with bronchiectasis who had been hospitalized in the Third Affiliated Hospital of Soochow University between September 2018 to December 2021. Dectin-1, IL-17 and GM were measured by enzyme-linked immunosorbent assays. Results: A total of 129 patients were analyzed in the study, of whom 33 had proven or probable IPA with bronchiectasis. The remaining 96 patients served as controls. The plasma Dectin-1 and IL-17 levels in the IPA group were significantly higher than that in the control group(P=0.005; P<0.001). The plasma GM, BALF GM, plasma Dectin-1 and IL-17 assays had sensitivities of 39.4%, 62.5%, 69.7% and 78.8%, respectively, and specificities of 89.2%, 91.5%, 72.9% and 71.9%, respectively. The sensitivity of Dectin-1 and IL-17 in plasma was higher than that in plasma and BALF GM. while the specificity is lower than that of plasma and BALF GM. The diagnostic sensitivity and specificity of plasma GM combined with IL-17 for IPA in bronchiectasis were greater than 80%. The combination of plasma GM and IL-17 can improve the sensitivity of the GM test, but does not reduce the diagnostic specificity. The plasma Dectin-1 and IL-17 showed positive linear correlations with the bronchiectasis severity Index(BIS) score in linear regression. Conclusions: Plasma Dectin-1 and IL-17 levels were significantly higher in bronchiectasis patients with IPA. The sensitivity of Dectin-1 and IL-17 was superior to that of GM for the diagnosis of IPA in patients with bronchiectasis. The combination of GM and IL-17 in plasma is helpful for the diagnosis of IPA in bronchiectasis patients who cannot tolerate invasive procedures.